2007
DOI: 10.1097/mat.0b013e318031af3b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fiber Bundle Rotation for Enhancing Gas Exchange in a Respiratory Assist Catheter

Abstract: Supplemental oxygenation and carbon dioxide removal through an intravenous respiratory assist catheter can be used as a means of treating patients with acute respiratory failure. We are beginning development efforts toward a new respiratory assist catheter with an insertional size <25F, which can be inserted percutaneously. In this study, we evaluated fiber bundle rotation as an improved mechanism for active mixing and enhanced gas exchange in intravenous respiratory assist catheters. Using a simple test appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…The current study used the same rotating fiber bundle PRAC as used in our past gas exchange studies (17). The prototype consisted of 750 microporous hollow fiber membranes (x30‐240, 240/300 µm internal diameter (ID)/outer diameter, Celgard, Inc., Charlotte, NC, USA) wrapped around a supporting cylindrical rod to create 10 layers of fiber.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study used the same rotating fiber bundle PRAC as used in our past gas exchange studies (17). The prototype consisted of 750 microporous hollow fiber membranes (x30‐240, 240/300 µm internal diameter (ID)/outer diameter, Celgard, Inc., Charlotte, NC, USA) wrapped around a supporting cylindrical rod to create 10 layers of fiber.…”
Section: Methodsmentioning
confidence: 99%
“…Deionized water at 37°C was circulated through the loop at 3 L/min. We chose water as our circulating fluid for simplicity and because our gas exchange studies in both water and blood showed similar effects of rotation speed on gas exchange (17). The difference between the index of refraction of the acrylic test section and water was sufficiently small that it did not distort the particle trajectory images in the thin gap between the fiber bundle and wall in the r ‐ z plane of flow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, efforts are moving forward with the development of an impeller percutaneous respiratory assist catheters (iPRAC) with an insertion size <25 Fr. [93] The limitation to the clinical application of this sort of a catheter is the ability to protect the vascular endothelium from rotating fibers.…”
Section: Conventional Respiratory Support For Acute Respiratory Distrmentioning
confidence: 99%